Hubungan Pola Konsumsi Gula, Garam dan Minyak Dengan Obesitas Sentral Pada Pegawai Pemerintah di Kantor Dinas Perpustakaan dan Kearsipan Daerah Provinsi Bengkulu : Hubungan Pola Konsumsi Gula, Garam dan Minyak Dengan Obesitas Sentral Pada Pegawai Pemerintah di Kantor Dinas Perpustakaan dan Kearsipan Daerah Provinsi Bengkulu - Mellisa, Mellisa; Simanjuntak, Betty Yosephin; Krisnasary, Arie (Amerta Nutrition, 2023)
Background: Central obesity manifests as the accumulation of adipose tissue in abdominal (visceral). The assessment of this condition often employs abdominal circumference (AC) as a commonly utilized metric. The increasing prevalence of central obesity is linked to dietary habits encompassing simple carbohydrates, fiber, and protein, environment, behavior, and genetic factors. Objectives: This study aimed to determine the relationship between sugar, salt, and oil consumption patterns and central obesity in employees. Methods: This research was an observational study with a cross-sectional design on 35 employees. Data collection included sugar, salt, and oil consumption patterns collected using a semi-quantitative food frequency questionnaire (SQ-FFQ), and central obesity was obtained by measuring abdominal circumference using measuring tape, then statistical analysis using the Chi-square test. Results: Most respondents had unhealthy consumption patterns of sugar, salt, and oil that were 71.4%, 62.9%, and 82.9%, respectively. There was a significant relationship between consumption patterns of sugar (p=0.002), salt (p=0.033), oil (p=0.019) and the proportion of central obesity in employees at the Regional Library and Archives Office of Bengkulu Province. Conclusions: Twenty-two employees experienced central obesity, with the majority surpassing daily sugar, salt, and oil intake recommendations as a notable risk factor. To mitigate this, Bengkulu Province Regional Library and Archives Office staff are advised to limit the consumption of sugar, salt, and oil-rich items such as salted fish, canned sardines, dried shrimp, instant chili sauce, soy sauce, instant noodles, palm oil, and coconut milk in their meals.